Effects of nitrogen addition on plant biomass and tissue elemental content in different degradation stages of temperate steppe in northern China. (31st July 2017) - Chen, Jin-Bin; Dong, Cheng-Cheng; Yao, Xiao-Dong; Wang, Wei
Abstract: Aims: Grassland degradation has become a common problem worldwide. Several studies have analyzed the effects of nitrogen (N) addition on plant growth in grasslands, but few have considered its effects on plant growth in degraded grasslands. The aim of this study was to evaluate the effects of N addition on plant growth in grasslands with different levels of degradation in Inner Mongolia, China. Methods: A 2-year field experiment was conducted to evaluate plant growth response to N addition in degraded grasslands on the Inner Mongolian Steppe. Grasslands with four levels of degradation were selected for N-addition treatments (0, 10, 20, 30, 40, 50 g N m −2 year −1 ). Important Findings: Aboveground biomass was increased by N fertilization in degraded grasslands, and N addition was significantly related to increased biomass in grasslands with severe degradation. However, N fertilization did not significantly affect belowground biomass. The effects of N addition on foliar nutrient concentrations in the same species differed among grasslands with different degradation levels. There was an inconsistent response to N addition between Sanguisorba officinalis and Vicia sepium in non-degraded grassland. There was a significant positive correlation between foliar N content and aboveground biomass in grasslands with different levels of degradation. Our results indicate that the effects of N addition on plant growth in grasslands differ according to the severity of degradation. We conclude that N fertilization may be an effective management technique for degraded grasslands in this area and may improve forage productivity in the short term.